Changes in physiological and stroke parameters during a maximal 400-m free swimming test in elite swimmers - Laffite, L. P.; Vilas-Boas, J. P.; Demarle, A.; Silva, J.; Fernandes, R.; Billat, V. L. (Canadian Journal of Applied Physiology, 2004)
The aim of this study was to analyse the variations of the metabolic and technical parameters during a maximal 400-m freestyle event. Seven trained male swimmers swam a maximal 400-m freestyle as if in competition (255.8 +/- 6.9 s). Intermediate time and stroke rate (SR) were recorded at each length (25 m). To estimate the changes in metabolic parameters during the 400-m event, they swam a 300-, 200-, and 100-m test set from each length of the 400-m event results, resting 90 min between each test. The exact speed at each length was given with a visual light pacer. Oxygen uptake (VO(2)) and blood lactate concentration ( [Lac]) were measured before and immediately after each test. VO(2) and [Lac] were stable during the 100-, 200-, and 300-m test but significantly higher (p < 0.05) during 400-m test. The estimated contribution of anaerobic metabolism (EsCANA ) during the first 100-m and the 400-m represented 45 % and 20 % of total energy output, respectively. Speed decreased significantly (p < 0.05) after the first 100-m and remained stable until the end. SR decreased significantly after the first 100-m, then increased until the end, while stroke length (SL) decreased linearly throughout the 400-m. During the first or the last 100-m, EsCANA was not correlated with the changes in V, SR, or SL between the second and the first 100-m, and between the fourth and the third 100-m, respectively. To conclude, this study showed that the swimmers were not able to maintain stable SL during the 400-m event. Thus, to sustain stable velocity and to compensate for the decrease in SL, swimmers increased SR throughout the last 300-m.